The Value of Lymphocyte to C-reactive Protein Ratio in Asymptomatic COVID-19 Cases in Pregnant Versus Non-Pregnant Women - Alaa Ibrahim Ali; Wassan Nori (Journal of Medical Sciences, 2023)
Background: Asymptomatic COVID-19 cases (ACC) had a key role in the deleterious spread of infection. Breaking the transmission chain by detecting ACC is an integral part of reducing adverse fetomaternal outcomes. The aims: we aimed to screen for ACC in women irrespective of pregnancy. Moreover, we tested the superiority of lymphocyte to C-reactive protein ratio (LCR), which is an inflammatory biomarker in relation to COVID-19 infection, and in distinguishing ACC. Materials and methods: A retrospective study recruited a hundred confirmed COVID-19 cases by PCR at the University Hospital. Participants were subdivided into two groups; Gr.1 (50 pregnant women at 37-41 weeks gestational age ) and Gr. 2 (50 non-pregnant women). They were age and body-mass index-matched. For all, we obtained demographics, clinical features, and lab tests including (hemoglobin(HB), White blood cells (WB) neutrophils, lymphocytes, platelets count, C-reactive (CRP), D-dimer, Alanine transaminase (ALT), Aspartate aminotransferase (AST), and renal function test. Additionally, LCR for both groups was assessed. Results: ACC, LCR were significantly lower in pregnant versus non-pregnant ( 44.83% vs. 72.42%)P -value=0.0001, LCR (230.07 vs.337.22) respectively. HB, platelets, and LCR levels were significantly lower among Gr1 compared to group 2. While the WBC, NEU, LYM, CRP, Alanine transaminase counts, creatinine, and D-dimer were significantly higher in Gr 1. The two groups scored no meaningful differences in the aspartate aminotransferase and blood urea. ROC calculated the LCR cutoff value in pregnant cases; at 232.8, with 53.9,90 % sensitivity and specificity. The area under the curve AUC was 0.69, P-value<0.005. However, LCR scored insignificant AUC 0.5, P=0.97 in determining ACC at a cutoff value of 291.14. Conclusion: A significantly reduced LCR in pregnant women underlies the infection’s severity compared to non-pregnant. However, the insignificant correlation of LCR to grammar symptoms in those affected makes LCR an unreliable marker in ACC detection; PCR is still the gold standard.